A business history of India : enterprise and the emergence of capitalism from 1700 - Roy, Tirthankar (New York : Cambridge University Press, 2018)
"In recent decades, private investment has led to an economic resurgence in India. But this is not the first time the region has witnessed impressive business growth. There have been many similar stories over the past 300 years. India's economic history shows that capital was relatively expensive. How, then, did capitalism flourish in the region? How did companies and entrepreneurs deal with the shortage of key resources? Has there been a common pattern in responses to these issues over the centuries? Through detailed case studies of firms, entrepreneurs, and business commodities, Tirthankar Roy answers these questions. Roy bridges the approaches of business and economic history, illustrating the development of a distinctive regional capitalism. On each occasion of growth, connections with the global economy helped firms and entrepreneurs better manage risks. Making these deep connections between India's economic past and present shows why history matters in its remaking of capitalism today"--
Machine generated contents note: Preface; List of Figures; List of Tables; List of Maps; List of Boxes; 1. Introduction; 2. The Baseline at 1700; 3. Indian Ocean Sphere 1700-1850; 4. Capital and Empire 1850-1930: Trade and Finance; 5. Capital and Empire 1850-1930: Industry; 6. State and Industrialization 1930-1950; 7. State and Industrialization 1950-1980; 8. Revival 1980-2000; 9. Capital and Globalization 2000-2015; 10. Conclusion; References; Index.
Includes bibliographical references (pages 266-284) and index.
Keywords: Business -- India -- History; Economic history; India -- Economic conditions; India -- Social conditions